Agriculture Changes During the Years of Independence in Uzbekistan - Hasanova Nishona Normurotovna (Genius Journals, 2023)
Following article deals with the changes in agriculture during the years of independence in Uzbekistan. The abolition of the cotton monopoly, the laws adopted by the Cabinet of Ministers on agriculture and land, and the works carried out within the framework of the decrees, decisions and orders of our president on agriculture are given as well.
Keywords: agriculture; irrigation; calendar; agrarian sector